2017
DOI: 10.1161/circgenetics.116.001537
|View full text |Cite
|
Sign up to set email alerts
|

Novel Variant in the ANK2 Membrane-Binding Domain Is Associated With Ankyrin-B Syndrome and Structural Heart Disease in a First Nations Population With a High Rate of Long QT Syndrome

Abstract: Background— Long QT syndrome confers susceptibility to ventricular arrhythmia, predisposing to syncope, seizures, and sudden death. While rare globally, long QT syndrome is ≈15× more common in First Nations of Northern British Columbia largely because of a known mutation in KCNQ1 . However, 2 large multigenerational families were affected, but negative for the known mutation. Methods and Results— … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 47 publications
2
50
0
Order By: Relevance
“…The loss-of-function variant was found to prohibit normal membrane targeting of NCX, presumably due to the altered localization of AnkB p.S646F. 38 Ichikawa et al also recently found possibly damaging variants in the MBD in isolated cases of arrhythmia. All other reported disease causing loss-of-function variants occur in the SBD, DD, or C-terminal domain.…”
Section: Human Ank2 Variantsmentioning
confidence: 99%
See 3 more Smart Citations
“…The loss-of-function variant was found to prohibit normal membrane targeting of NCX, presumably due to the altered localization of AnkB p.S646F. 38 Ichikawa et al also recently found possibly damaging variants in the MBD in isolated cases of arrhythmia. All other reported disease causing loss-of-function variants occur in the SBD, DD, or C-terminal domain.…”
Section: Human Ank2 Variantsmentioning
confidence: 99%
“…Normal localization of NCX and AnkB was also found to be disrupted in the MBD variant p.S646F, indicating that NCX localization is regulated by two AnkB domains – MBD and RD. 38 ANK2 variants have also been found to cause sinus node disease (SND), and AnkB heterozygous (AnkB +/− ) mice phenocopy human SND patients, presumably due to loss of AnkB-mediated organization and signaling in sinoatrial node (SAN) cells. 34 Another variant in ANK2 that disrupts the AnkB/βII-spectrin interaction (AnkB p.R990Q) causes severe arrhythmia phenotypes.…”
Section: Human Ank2 Variantsmentioning
confidence: 99%
See 2 more Smart Citations
“…The subsequent association of either Sptbn1 (275 kDa), or Itpr1 (310 kDa) would shift the mass to around 800 kDa. Both Sptan1 and Ank2 have a variety of binding domains where interactions with Kcc2 could occur, such as SH3 domains (Sptan1) (61) and the membrane binding domain containing the Ank repeat sequences of Ank2 (62), which has been shown to interact with other ion channels/transporters (63).…”
Section: Kcc2 Forms Stable Multi-protein Complexes In the Plasma Membmentioning
confidence: 99%